Komplikace po revizních operacích totálních endoprotéz kolena - Louda, Josef; Kubát, Pavel; Pilný, Jaroslav (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2020)
PURPOSE OF THE STUDY The failure of arthroplasties and above all the issue of infection and its detection have become an ever more frequently discussed problem. The purpose of our study was to determine the frequency and the type of complications after revision total knee arthroplasties and to compare them with the frequency of complications after primary implantations. MATERIAL AND METHODS In our group of patients followed up in the period from January 2007 to December 2016, in 50 patients the revision surgery was performed for aseptic loosening and in 24 patients for deep infection. In the case of revision surgery for aseptic loosening, in 18 patients original sterilised components were used as a spacer, in 6 patients an articulating cement spacer was applied. Only the complications resulting in the performance of further revision were included in the statistics. A total of 13 patients underwent a primary implantation at another centre. The number of revisions and the reason for implant failure were monitored. The results were compared with the frequency of revision surgeries after primary total knee arthroplasty, of which 2,436 were carried out in the referred to period. RESULTS Of 2,436 primary endoprostheses, altogether 3.1 % failed. In 50 (2.1 %) patients aseptic loosening was reported, 24 patients (1 %) suffered from infection. The median time from primary implantation to revision was 11 years for aseptic loosening, 2 years for infection. The most frequent cause of failure was aseptic loosening. In the group of patients who underwent a revision surgery for aseptic loosening, another revision was necessary in 6 cases (12 %), in the group of patients after the two-stage revision surgery for infection, in 9 cases (37.5 %). The most frequent reason for revision surgery was infection - in both the groups this was the reason for 67 % of revision surgeries. DISCUSSION Our results obtained with respect to primary as well as revision surgeries for aseptic loosening correspond with the results reported by other authors. In the case of two-stage revision implantation, the reported frequency of recurrent infections is the same, the frequency of revision surgeries for aseptic causes is slightly lower in our group. The most frequent causes of revision surgery are also in agreement. In the case of primary implantation, the patients most frequently suffer from aseptic loosening, after revision surgeries another revision surgery is most often performed due to infection. The literature refers to studies suggesting the potential use of original components as a spacer with the same success rate as that achieved with the cement spacer. The original components produced good results in two thirds of two-stage revision implantations, which is why we can agree with these studies. CONCLUSIONS The results clearly show a noticeable increase in the frequency of complications in revision surgeries compared to primary surgeries. In comparison with primary implantations, a subsequent revision after the revision implantation for aseptic loosening was necessary three times more frequently, after the two-stage revision implantation for infection it was ten times more frequently. As the most problematic complication can be considered the infection in case of primary as well as revision interventions. It is obvious that aseptic loosening of the primary implant usually occurs later (the median of 11 years) than the development of deep infection (the median of 2 years). Key words: total knee arthroplasty, revision, failure, complications, aseptic loosening, infection, spacer.
Keywords: reoperace; Arthroplasty, Replacement, Knee; Humans; Surgical Wound Infection; infekce chirurgické rány; selhání protézy; Prosthesis Failure; následné studie; Follow-Up Studies; Reoperation; lidé; totální endoprotéza kolene